Historical profile of gender in Turkish veterinary education - Gul, Raziye Tamay Basagac; Ozkul, Tural; Akcay, Aytac; Ozen, Abdullah (Univ Toronto Press Inc, 2008)
Women in Turkey were first given the opportunity to attend schools of higher education in 1914. Following the establishment of the Turkish Republic in 1923, a number of social, judicial, and economic reforms took place that enabled women to participate actively in both the public and private sectors, and, as a consequence, the number of women students in higher education increased rapidly. The first woman graduated from the veterinary school in Ankara in 1935, becoming the first female veterinarian in the country. Since that time, the number of female veterinary graduates in Turkey has steadily increased.
Keywords: Turkey; veterinary education; gender; feminization